Risk Factors and Brain Metabolic Mechanism of Sleep Disorders in Autoimmune Encephalitis - Liu, Xiao; Yu, Tingting; Zhao, Xiaobin; Yu, Ping; Lv, Ruijuan; Wang, Chunxue; Ai, Lin; Wang, Qun (Frontiers in Immunology, 2021)
Background: Sleep disorders (SD) in autoimmune encephalitis (AE) have received little attention and are poorly understood. We investigated the clinical characteristics, risk factors, cerebral metabolic mechanism of SD in AE. Methods: Clinical, laboratory, and imaging data were retrospectively reviewed in 121 consecutively patients with definite AE. The risk factors for SD in AE were estimated by logistic regression analysis. Group comparisons based on 18F-fluorodeoxy-glucose positron emission tomography (18F-FDG-PET) data were made between patients with and without SD, to further analyze potential brain metabolic mechanism of SD in AE. Results: 52.9% patients (64/121) with SD were identified. The multivariate logistic model analysis showed that smoking (OR, 6.774 [95% CI, 1.238-37.082]; P = 0.027), increased HAMD score (OR, 1.074 [95% CI, 1.002-1.152]; P = 0.045), hyperhomocysteinemia (OR, 2.815 [95% CI, 1.057-7.496]; P = 0.038), elevated NSE level (OR, 1.069 [95% CI, 1.007-1.135]; P = 0.03) were independently correlated with higher risk of SD in AE patients. Contrastingly, high MoCA score (OR, 0.821 [95% CI, 0.752-0.896]; P < 0.001) was associated with lower risk of SD in AE subjects. Compared to controls, AE patients had less total sleep time, less sleep efficiency, longer sleep latency, more wake, higher percent of stage N1, lower percent of stage N3 and rapid eye movement, and more arousal index in non-rapid eye movement sleep (P < 0.05 for all). Voxel-based group comparison analysis showed that, compared to patients without SD, patients with SD had increased metabolism in basal ganglia, cerebellum, brainstem, median temporal lobe, thalamus and hypothalamus (P<0.05, FDR corrected), decreased metabolism in superior frontal gyrus, medial frontal gyrus and posterior cingulate cortex (P < 0.001, uncorrected). These results were confirmed by region of interest-based analysis between PET and sleep quality. Conclusion: Smoking, increased HAMD score, hyperhomocysteinemia, elevated NSE level were correlated with higher risk of SD. High MoCA score was associated with lower risk of SD in AE subjects. Moreover, a widespread metabolic network dysfunction may be involved in the pathological mechanism of SD in AE.